Phase transition mechanism of hexagonal graphite to hexagonal and cubic diamond: ab initio simulation. (11th August 2021) - Mittal, Ranjan; Gupta, Mayanak Kumar; Chaplot, Samrath Lal
Abstract: Ab initio molecular dynamics simulations are used to elucidate the mechanism of the phase transition in shock experiments from hexagonal graphite (HG) to hexagonal diamond (HD) or to cubic diamond (CD). The transition from HG to HD is found to occur swiftly in very small time of 0.2 ps, with large cooperative displacements of all the atoms. We observe that alternate layers of atoms in HG slide in opposite directions by 1/6 along the ±[2, 1, 0], which is about 0.7 Å, while simultaneously puckering by about ±0.25 Å perpendicular to the a – b plane. The transition from HG to CD occurred with more complex cooperative displacements. In this case, six successive HG layers slide in pairs by 1/3 along [0, 1, 0], [−1, −1, 0] and [1, 0, 0], respectively along with the puckering as above. We have also performed calculations of the phonon spectrum in HG at high pressure, which reveal soft phonon modes that may facilitate the phase transition involving the sliding and puckering of the HG layers. We have further calculated the Gibbs free energy, including the vibrational energy and entropy, and derived the phase diagram between HG and CD phases.